Implementation of Human as Bridge in Advocacy of Cigarette Area in Universitas Pembangunan Nasional “Veteran” Jawa Timur - Fauzan Aliwarman; Eko Wahyudi (Future Science)
Universitas Pembangunan Nasional “Veteran” Jawa Timur (UPN Jawa Timur) as a pioneering development undergraduate campus, where the interaction of the teaching and learning process of the academic community has declared itself as a non-smoking campus area based on the spirit of Government Regulation number 109 of 2012 concerning the safeguarding of substances containing substances addictive in the form of tobacco products for health and Surabaya City Regulation Number 5 of 2008 concerning no-smoking areas and limited smoking. However, since the rector's decision regarding the inauguration of UPN Jawa Timur as a non-smoking campus area from 2011 to 2018 results were not encouraging. He still got a part of the academics who smoke in random places, lack of internal arrangements related to non-smoking areas, the absence of maps without smoking areas and limited smoking, low socialization for the academic community, lack of advocacy for customers without cigarettes. As well as still not maximizing the function of internal supervision which is the estuary of the problems that plague the realization of a beautiful, healthy and free from cigarette smoke. Ideally, the campus is the front guard in the success of healthy behavior without smoking for young people in Indonesia. Advocacy is needed to strengthen the rules for the implementation of non-smoking areas in UPN Jawa Timur, a strategic effort to limit smokers active in certain areas, improve humanist supervision procedures and not forget to look at the basis of coaching through a personality approach for violators from the academic community.